The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/cnma.201800009
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Mesoporous Titania Nanoparticles with Controlled Porosity and Connectivity for Studying the Photovoltaic Properties in Perovskite Solar Cells

Abstract: Mesoporous titania (TiO2) nanoparticles (NPs) were synthesized by treating prehydrolyzed titanium precursors with polyethylene glycol (PEG). By varying the amount of PEG, their different physical properties were tuned appropriately in terms of surface area, pore size/volume, and electrical conductivity. By increasing the amount of PEG in TiO2, the surface area and pore volume of mesoporous TiO2 increased, and no direct correlation with the photovoltaic performance of perovskite solar cells was observed. In com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…It was indeed demonstrated that the porosity of the titania scaffold, which mainly depends on the dimensions of spherical nanoparticles, determines both the perovskite coverage and crystallinity [ 98 , 99 , 100 , 101 , 102 , 103 ]. Improved coverage of the titania scaffold, obtained by increasing the porosity, gives rise to better light harvesting capabilities and hence results in higher short circuit current density generation [ 101 , 102 , 104 ]. Another consequence of the improvement of the TiO 2 scaffold coverage is the reduction of undesired electron–hole recombination, which occurs at the interface between electron and hole-transport layers; accordingly, a more effective capability of charge extraction from the perovskite was demonstrated by measuring the photoluminescence intensity, which decreases for increased titania film porosity while maintaining the same thickness.…”
Section: Photovoltaic Energy Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was indeed demonstrated that the porosity of the titania scaffold, which mainly depends on the dimensions of spherical nanoparticles, determines both the perovskite coverage and crystallinity [ 98 , 99 , 100 , 101 , 102 , 103 ]. Improved coverage of the titania scaffold, obtained by increasing the porosity, gives rise to better light harvesting capabilities and hence results in higher short circuit current density generation [ 101 , 102 , 104 ]. Another consequence of the improvement of the TiO 2 scaffold coverage is the reduction of undesired electron–hole recombination, which occurs at the interface between electron and hole-transport layers; accordingly, a more effective capability of charge extraction from the perovskite was demonstrated by measuring the photoluminescence intensity, which decreases for increased titania film porosity while maintaining the same thickness.…”
Section: Photovoltaic Energy Conversionmentioning
confidence: 99%
“…Another consequence of the improvement of the TiO 2 scaffold coverage is the reduction of undesired electron–hole recombination, which occurs at the interface between electron and hole-transport layers; accordingly, a more effective capability of charge extraction from the perovskite was demonstrated by measuring the photoluminescence intensity, which decreases for increased titania film porosity while maintaining the same thickness. It was also reported that when maintaining the same morphology, when the titania film thickness exceeds an optimal value, the transport characteristics of the electrode [ 104 ] degrade because the perovskite coverage decreases, allowing recombination processes, and also, as widely discussed above, the number of interparticles connections decreases, lengthening the electron path. Moreover, many papers report on the impact of the perovskite grain size on the charge recombination processes not explicitly addressing the role of the titania scaffold morphology [ 100 , 105 , 106 ] but showing the improved performance of cells with larger grains, which are less affected by trap-assisted recombination at the grain boundaries.…”
Section: Photovoltaic Energy Conversionmentioning
confidence: 99%
“…Renewable resources are produced in abundance on Earth, and include hydropower [ 71 , 72 ], wind power [ 73 ], and solar power [ 74 , 75 ]. However, harvesting these energies often requires large and complex infrastructures, which make it challenging to harness renewable energy sources in miniaturized and portable electronics.…”
Section: Cellulose-based Composites For Energy Conversionmentioning
confidence: 99%
“…Up to now, only few reports have focused on optimizing the pore size of mesoscopic layers to improve the photovoltaic performance of the PSCs [73,74] and this strategy needs to be further explored. Naturally, methods to passivate the GBs and reduce trap densities there also represent a promising approach to reduce the V OC gap with the radiative limit.…”
Section: Outlining Promising Strategies To Improve the Pce Of Cpscsmentioning
confidence: 99%